2015
DOI: 10.1021/jacs.5b03553
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Superheterojunction Polymers via Direct Polycondensation: Segregated and Bicontinuous Donor–Acceptor π-Columnar Arrays in Covalent Organic Frameworks for Long-Lived Charge Separation

Abstract: By developing metallophthalocyanines and diimides as electron-donating and -accepting building blocks, herein, we report the construction of new electron donor-acceptor covalent organic frameworks (COFs) with periodically ordered electron donor and acceptor π-columnar arrays via direct polycondensation reactions. X-ray diffraction measurements in conjunction with structural simulations resolved that the resulting frameworks consist of metallophthalocyanine and diimide columns, which are ordered in a segregated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
207
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(221 citation statements)
references
References 46 publications
3
207
1
3
Order By: Relevance
“…[70] Typically,w hen donor and acceptorm olecules are cocrystallized, they stack on top of each other,c ausing rapid combination of chargec arriers and very low efficiencies. [73] This study found that, when the acceptor wash eldc onstant and the metal was changed, the charge-separation lifetimes weres imilar;h owever,g iven as ingle acceptor,t he identityo ft he metal did affect the charge lifetimes. This createsv ertically ordered p-n heterojunctions and av ery large donor-acceptor interface, which should significantly increase the photoconductivity of the material,w ithout the need for an added dopant.…”
Section: Cofs For Photovoltaic Applicationsmentioning
confidence: 83%
“…[70] Typically,w hen donor and acceptorm olecules are cocrystallized, they stack on top of each other,c ausing rapid combination of chargec arriers and very low efficiencies. [73] This study found that, when the acceptor wash eldc onstant and the metal was changed, the charge-separation lifetimes weres imilar;h owever,g iven as ingle acceptor,t he identityo ft he metal did affect the charge lifetimes. This createsv ertically ordered p-n heterojunctions and av ery large donor-acceptor interface, which should significantly increase the photoconductivity of the material,w ithout the need for an added dopant.…”
Section: Cofs For Photovoltaic Applicationsmentioning
confidence: 83%
“…Herein, we show synthesis and electrical properties of a new conductive 2D MOF Cu‐CuPc in which tetracatechol copper phthalocyanines (CuPcOH) with catechol‐type ligands are bridged by square‐planar copper(II) ions (Figure ). Phthalocyanine is chosen as the planar bridging unit because of its redox activity and good carrier transport ability based on the large delocalized π system . The catechol derivatives are known to form square‐planar complexes with metal ions which show redox activity, based on the reversible interconversions between catechol, semiquinone, and quinone forms .…”
Section: Figurementioning
confidence: 99%
“…A D MPc -A DI COF series based on metallophthalocyanine electron donor and diimide chromophore electron acceptor subunits featured a so-called superheterojunction where two types of ordered donor-acceptor heterojunctions are present within the COF structure. [22] The well-defined organization of the electron donor and acceptor stacks provides a distinct chemical and physical environment that can facilitate electron transfer, charge separation, and allow for extended charge transfer lifetimes. For example, a long charge separated state lifetime of 33 µs for D CuPc -A DI COF in this series was detected by the TR-ESR measurements.…”
Section: Electroactive and Photoactive Cof Bulk Materialsmentioning
confidence: 99%